Psycho-social predictors of achievement in multicultural concepts in social studies among secondary school students, in Ijebu South Local Government, Ogun State (2016)
This study examined the extent to which psycho-social factors predicted students achievement in Social Studies, adopting a correlational research type and multi-stage sampling technique. Three instruments namely: Teacher Questionnaire (r = 0.89); Student Questionnaire (r = 0.78) and Social studies Achievement Test (KR20 = 0.72) were used to collect data from 350 respondents drawn from ten junior secondary schools in Ogun state. Four research questions were set and answered using multiple regression analysis. Students' self-concept (r = 0.631; P < .05) and Students' peer pressure (0.681; P < .05) have high positive significant relationship with Social studies achievement scores. A statistically significant linear relationship exists between the predictor variables. The predictors accounted for 64.5% of the total variance observed in students' achievement in social studies. Influence of Students' Peer Pressure β = .202; t (324) = 4.104; p < .05) was most influential followed by Students' Motivation (β = .139; t (324) = 3.476; p < .05). Also, Students' Self-concept β = .151; t (324) = 3.292; p < .05) and Teachers' Social Interaction (β = -.833; t (324) = -2.842; p < .05). The result indicated that peer pressure, students' motivation, students' self-concept and teachers' social interaction have a significant predictive ability of academic gains, therefore parents and teachers should watch the kind of friends keeping by their children/ students. Also, students should be highly motivated as this promotes strongly academic gains through adequate rewards and reinforcement in the classroom.